The ABC Guide to Fluorescent Toolsets for the Development of Future Biomaterials - Ferdinandus,; Arai, Satoshi (Frontiers in Bioengineering and Biotechnology, 2019)
In recent decades, diversified approaches using nanoparticles or nano-structured scaffolds have been applied to drug delivery and tissue engineering. Thanks to recent interdisciplinary studies, the materials developed have been intensively evaluated at animal level. Despite these efforts, less attention has been paid to what is really going on at the subcellular level during the interaction between a nanomaterial and a cell. As the proposed concept becomes more complex, the need for investigation of the dynamics of these materials at the cellular level becomes more prominent. For a deeper understanding of cellular events, fluorescent imaging techniques have been a powerful means whereby spatiotemporal information related to cellular events can be visualized as detectable fluorescent signals. To date, several excellent review papers have summarized the use of fluorescent imaging toolsets in cellular biology. However, applying these toolsets becomes a laborious process for those who are not familiar with imaging studies to engage with owing to the skills gap between them and cell biologists. This review aims to highlight the valuable essentials of fluorescent imaging as a tool for the development of effective biomaterials by introducing some cases including photothermal and photodynamic therapies, or something similar. This distilled information will be a convenient short-cut for those who are keen to fabricate next generation biomaterials.